Education for extinction American Indians and the boarding school experience, 1875 - 1928 - Adams, David W. (Univ. Press of Kansas, 1995)
Education for Extinction offers the first comprehensive account of this dispiriting effort. Much more than a study of federal Indian policy, this book vividly details the day-to-day experiences of Indian youths living in a "total institution" designed to reconstruct them both psychologically and culturally. Based upon extensive use of government archives, Indian and teacher autobiographies, and school newspapers, it is essential reading for anyone interested in Western history, Native American studies, American race relations, educational history, or multi-culturalism
Keywords: Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1875-1928; Internats - États-Unis - Histoire - 19e siècle; Internats - États-Unis - Histoire - 20e siècle; Jeunesse indienne d'Amérique - Acculturation - États-Unis; Jeunesse indienne d'Amérique - Politique gouvernementale - États-Unis; Jeunesse indienne d'Amérique - Éducation - États-Unis; Éducation - Politique gouvernementale - États-Unis - Histoire; Erziehung; Geschichte; Politik; Boarding schools -- United States -- History -- 19th century; Boarding schools -- United States -- History -- 20th century; Education and state -- United States -- History; Indian youth -- Cultural assimilation -- United States; Indian youth -- Education -- United States; Indian youth -- Government policy -- United States; Heimschule; Indianer; États-Unis - Politique sociale; États-Unis - Relations raciales; USA; United States -- Race relations; United States -- Social policy